Correction: THF-enabled PtBr2-catalyzed desymmetric hydrogenative [3 + 2] cycloaddition of 2-alkynylbenzaldehyde-tethered cyclohexadienones. Issue 14 (20th June 2022) - Hu, Rui; Chen, Jichao; Wang, Zeliang; Shang, Dandan; Yu, Lei; Wai Hong Chan, Philip; Rao, Weidong
Abstract : Correction for 'THF-enabled PtBr2 -catalyzed desymmetric hydrogenative [3 + 2] cycloaddition of 2-alkynylbenzaldehyde-tethered cyclohexadienones' by Rui Hu et al., Org. Chem. Front., 2022, ; https://doi.org/10.1039/d2qo00593j .